The sandman book of dreams - Gaiman, Neil; Kramer, Ed (HarperTorch, 1996)
Fantasy stories. In Will Shetterly's Splatter, killers decide to show a novelist how it's really done, Karen Haber's A Bone Dry Place is set in a suicide-prevention clinic, and in John Ford's Chain Home, Low a sleeping virus strikes a group of wartime pilots.